2012
DOI: 10.1007/s11033-012-1681-1
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of the Cinnamon Bittern, Ixobrychus cinnamomeus (Pelecaniformes: Ardeidae): sequence, structure and phylogenetic analysis

Abstract: Ixobrychus cinnamomeus is a member of the large wading bird family, known as Ardeidae. In the present study, we determined the complete mitochondrial genome of I. cinnamomeus for use in future phylogenetic analysis. This circular mitochondrial genome is 17,180 bp in length and composed of 13 protein-coding genes, 22 tRNA genes, two rRNA genes and one putative control region. Three conserved domains and a minisatellite of 17 nucleotides with 22 tandem repeats were detected at the end of the control region. Phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
7
29
0
Order By: Relevance
“…The AT and GC skews, which can be calculated as (A-T) / (A+T) or (G-T) / (G+T) (Perna and Kocher, 1995), for the complete mitochondrial genome of G. canorus are 0.11 and -0.38, respectively, showing a strong bias against guanine. This phenomenon has also been reported in other birds (San Mauro et al, 2004;He et al, 2009;Kan et al, 2010a,b;Zhang et al, 2012 Genes encoded on the heavy or light strands are shown outside or inside the circular gene map, respectively. The inner ring displays the GC content.…”
Section: Genome Organization and Base Compositionsupporting
confidence: 76%
See 4 more Smart Citations
“…The AT and GC skews, which can be calculated as (A-T) / (A+T) or (G-T) / (G+T) (Perna and Kocher, 1995), for the complete mitochondrial genome of G. canorus are 0.11 and -0.38, respectively, showing a strong bias against guanine. This phenomenon has also been reported in other birds (San Mauro et al, 2004;He et al, 2009;Kan et al, 2010a,b;Zhang et al, 2012 Genes encoded on the heavy or light strands are shown outside or inside the circular gene map, respectively. The inner ring displays the GC content.…”
Section: Genome Organization and Base Compositionsupporting
confidence: 76%
“…Most tRNA genes were identified using tRNAscan-SE 1.21 (Schattner et al, 2005) using the 'cove only' search mode, with the vertebrate mitochondrial genetic code and 'mito/chloroplast' source. A number of tRNA genes not identified using tRNAscan-SE 1.21 were identified by proposed secondary structures and anti-codons (Zhang et al, 2012). The gene map of the complete mitochondrial genome of G. canorus was initially generated by OGDRAW (Lohse et al, 2007) and then modified manually.…”
Section: Sequence Analysismentioning
confidence: 99%
See 3 more Smart Citations